On the Role of Metamodeling in Software Engineering - Brito e Abreu, F. (10th Int'l Conference on Computational Intelligence and Software Engineering (CiSE 2018), 2018)
Metamodeling techniques have played a major role in the last two decades in setting up the foundations for the systematic, disciplined and quantifiable approaches that are required in developing, operating and maintaining software systems, in other words, in what our community decided to call “Software Engineering”. This talk will present an insider’s view on the application of metamodeling techniques in several knowledge areas of the Software Engineering Body of Knowledge (SWEBOK), where Fernando’s QUASAR research group has developed pioneering work. He will review and discuss the relevance of the application of metamodel-based techniques in the ten major SWEBOK knowledge areas (Software Requirements, Software Design, Software Construction, Software Testing, Software Maintenance, Software Configuration Management, Software Engineering Management, Software Engineering Process, Software Engineering Models and Methods, Software Quality). Last, but not the least, Fernando will present his view on the role of metamodel-based techniques in the future of Software Engineering.